Relationship between flatwater kayak performance and energy supply capacity - Nakagaki, K.; Yoshioka, T.; Nabekura, Y. (Japanese Journal of Physical Fitness and Sports Medicine, 2007)
The purpose of this study was to investigate the relationship between 2-min kayak ergometer performance (KEP) and energy supply capacity. Seventeen (male: 9, female: 8) kayak paddlers completed a maximal incremental test to determine aerobic capacity {maximal oxygen uptake (VO_<2max>) and lactate threshold (LT)} , and a 2-min all-out test to measure performance and anaerobic capacity {maximal accumulated oxygen deficit (MAOD)}. In addition, total energy supply capacity was estimated by these variables [{(T-score of VO_<2max>+T-score of LT)/2+T-score of MAOD} /2], Oxygen uptake and blood lactate concentrations were continuously measured during the incremental test and at the completion of both tests. These tests were conducted on an air-braked kayak ergometer. Unlike the previous research, no significant relationships were found between KEP and VO_<2max> and LT in either male or female. MAOD correlated with KEP in female (r=0.75, p<0.05), but not in male. On the other hand, there was a significant correlation between KEP and total energy supply capacity (r=0.89, p<0.05, both male and female). In conclusion, total energy supply capacity accounted for a large part of KEP. These results indicate that flat-water kayak paddlers need to develop both aerobic and anaerobic capacities.